Hospital-acquired pneumonia due to Achromobacter xylosoxidans in the elderly: A single-center retrospective study in Beijing - Chao Liu; Jun Guo; Weifeng Yan; Yi Jin; Fei Pan; Xiangqun Fang; Long Qin; Changting Liu (Journal of Infection in Developing Countries)
Introduction: Achromobacter xylosoxidans has been reported in several countries; however, hospital-acquired pneumonia (HAP) due to this organism in elderly patients in China remains rare. Methodology: HAP due to Achromobacter xylosoxidans identified at the General Hospital of the People's Liberation Army in Beijing from January 2008 to October 2011 was studied. Detailed clinical manifestations were collected. To study the clinical risk factors for the imipenem-resistant strain, patients were divided into two groups: imipenem-resistant (21 cases) and imipenem-nonresistant (20 cases). Univariate and multivariate logistic regression were used. Results: All patients were > 75 years of age, and 92.7% (38/41) were male. Nine patients died 30 days after infection. The mean acute physiology and chronic health evaluation (APACHE) II score and sequential organ failure assessment (SOFA) were 23.66 ± 7.71 and 6.93 ± 2.47, respectively. Almost all strains were resistant to aminoglycosides. However, the strains showed significant sensitivity to minocycline (MIN), piperacillin-tazobactam (PTZ), and cefoperazone-sulbactam (SCF). Compared with the imipenem-nonresistant group, more patients with imipenem-resistant infection had the following characteristics: use of an intubation, use of a proton-pump inhibitor (PPI), chronic obstructive pulmonary disease (COPD), and coronary artery disease (CHD). Among the four risk factors, COPD and CHD remained independent risk factors in the multivariate analysis. Conclusions: HAP due to Achromobacter xylosoxidans occurred in severely ill elderly patients with a long-term indwelling catheter and many underlying diseases. Effective treatment of imipenem-resistant organisms is challenging. SCF, PTZ, and MIN may be useful for imipenem-resistant Achromobacter xylosoxidans.